Population pharmacokinetics of free flucloxacillin in patients treated with oral flucloxacillin plus probenecid. Issue 12 (21st May 2021) - Drennan, Philip G.; Green, Jared K.; Gardiner, Sharon J.; Metcalf, Sarah C. L.; Kirkpatrick, Carl M. J.; Everts, Richard J.; Zhang, Mei; Chambers, Stephen T.
Aims: Oral flucloxacillin may be coadministered with probenecid to reduce flucloxacillin clearance and increase attainment of pharmacokinetic–pharmacodynamic (PK/PD) targets. The aims of this study were to develop a population PK model of free flucloxacillin when administered orally with probenecid, and to identify optimal dosing regimens for this combination. Methods: We performed a prospective observational study of adults (45 participants) treated with oral flucloxacillin 1000 mg and probenecid 500 mg 8‐hourly for proven or probable staphylococcal infections. Steady‐state mid‐dose‐interval flucloxacillin measurements (45 concentrations) were combined with existing data from a crossover study of healthy participants receiving flucloxacillin with and without probenecid (11 participants, 363 concentrations). We developed a population pharmacokinetic model of free flucloxacillin concentrations within Monolix, and used Monte Carlo simulation to explore optimal dosing regimens to attain PK/PD targets proposed in the literature (free drug time above minimum inhibitory concentration). Results: Flucloxacillin disposition was best described by a 1‐compartment model with a lag time and first‐order absorption. Free flucloxacillin clearance depended on probenecid, allometrically‐scaled fat free mass (FFM) and estimated glomerular filtration rate (eGFR). Predicted PK/PD target attainment was suboptimal with standard dosing regimens with flucloxacillin alone, but substantially improved in the presence of probenecid. Conclusion: The simulation results reported can be used to identify dose regimens that optimise flucloxacillin exposure according to eGFR and FFM. Patients with higher FFM and eGFR may require the addition of probenecid and 6‐hourly dosing to achieve PK/PD targets. The regimen was well‐tolerated, suggesting a potential for further evaluation in controlled clinical trials to establish efficacy.